Friction data of simulated basaltic fault gouge under hydrothermal conditions [updated] - Okuda, Hanaya (Utrecht University, 2022)
We performed friction experiments on simulated basaltic gouge under hydrothermal conditions to investigate roles of subducting oceanic crust on seismogenesis in subduction zones. In this dataset, we report raw data, processed data after removal of seal friction effects, velocity dependence of friction coefficients, and the processing script for each experiment.

The data is provided in 13 zip-files for 13 experiments. Detailed information about the files in these zip-files as well as information on how the data is processed is given in the explanatory file Okuda-et-al-2022-Data-Description.pdf.

A new version of this data package has been published and can been found here: https://public.yoda.uu.nl/geo/UU01/Q0VVEX.html
Keywords: Rock and melt physical properties; friction experiments; simulated basaltic fault gouge; hydrothermal conditions; subducting oceanic crust; megathrust earthquakes; EPOS; multi-scale laboratories; rock and melt physical properties; basalt (fine-grained); Rotary Shear; Friction